2020
DOI: 10.1038/s41598-020-68394-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tumor mutational burden: correlation of five large gene panels with whole exome sequencing

Abstract: Outcome of immune checkpoint inhibition in cancer can be predicted by measuring PDL1 expression of tumor cells. Search for additional biomarkers led to tumor mutational burden (TMB) as surrogate marker for neoantigens presented. While TMB was previously determined via whole exome sequencing (WES), there have been approaches with comprehensive gene panels as well. We sequenced samples derived from formalin-fixed tumors, a POLE mutated cell line and standard DNA by WES and five different panels. If available, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Several studies have reported the development of methods for TMB calculation based on commercial NGS panels 43 , 44 . However, to the best of our knowledge, there is only one study where “in silico” tools were used to select genes for TMB prediction 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the development of methods for TMB calculation based on commercial NGS panels 43 , 44 . However, to the best of our knowledge, there is only one study where “in silico” tools were used to select genes for TMB prediction 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The challenge of interpreting TMB scores is further complicated by the availability of multiple diagnostic assays. It is unlikely that a single TMB threshold could uniformly be applied to all assays (11,12). Blood based cfDNA offers a more convenient approach to assess TMB and potentially overcome the problem of tumor heterogeneity, but fewer clinical studies have validated this approach.…”
Section: What Is Tmb?mentioning
confidence: 99%
“…High costs, extensive time-consuming analysis, and high amounts of DNA requirements for WES are challenging for daily routine TMB assessment. Therefore, gene panels may be preferable, because they are less cost-intensive, require lower input of DNA, and have an overall shorter turnaround time [12,13]. With increasing interest in TMB as a biomarker for response to ICI therapies, many commercial providers developed their own panel-based TMB assays, to be performed by molecular diagnostic labs in-house [13].…”
Section: Methods For Measuring Tumor Mutational Burden (Tmb)mentioning
confidence: 99%
“…Therefore, gene panels may be preferable, because they are less cost-intensive, require lower input of DNA, and have an overall shorter turnaround time [12,13]. With increasing interest in TMB as a biomarker for response to ICI therapies, many commercial providers developed their own panel-based TMB assays, to be performed by molecular diagnostic labs in-house [13]. Various challenges arise, impacting TMB determination: In the course of implementation of complex assays for TMB determination, factors like composition, distribution, and size of gene panels, influence of sequencing platforms, genomic coverage, bioinformatics evaluation, and definition of thresholds are becoming increasingly important.…”
Section: Methods For Measuring Tumor Mutational Burden (Tmb)mentioning
confidence: 99%